Identifkasi dan Inventarisasi Permasalahan Pelestarian Situs Makam Megalitikum di Distrik Mulyosari, Kecamatan Malangsari, Kabupaten Banyuwangi, Jawa Timur - Uji Nugroho Winardi; Agus Suwignyo; Baha’Uddin Baha’Uddin; Sri Margana (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Te existence of ancient grave sites in Banyuwangi save the potential of historical data to uncover the origins of Javanese civilization. However, the sites have been damaged by the activity of looting graves in the last ffteen years. Tis Community Engagement Activity aims to identify socio-economic issues and the substance of the object of the site study to stop looting and raise the potential of ancient tombs academically and politically concerning historical heritage management policies, as well as ocioeconomically for the local community. Community Engagement Activities was conducted in November 2015. Te team found that the looting of grave sites by residents was motivated by economic problems. Nevertheless, the problem network is rooted in the political aspect of the absence of a policy that places the ancient site’s grave as an area of cultural heritage. Tis issue is closely related to the low level of awareness of government and citizens. In addition, there are complex issues concerning the ownership and management of the land area of the grave site, which is a coﬀee plantation.